Cyto-histopathological study of Mediastinal lesions - N Bhattarai (Association of Clinical Pathologists of Nepal, 2016)
Background: Broad ranges of non-neoplastic and neoplastic lesions are encountered in mediastinum depending on the patient's age and anatomical site. This study was performed to review our institutional experience of mediastinal masses and to compare the results with various other studies. Materials and Methods: This was a retrospective study conducted on 112 patients with mediastinal masses who underwent fine needle aspiration cytology and/or biopsy from 14th April 2009 to 4th March 2014 in Department of Pathology, Institute of Medicine, Tribhuvan University Teaching Hospital. Results: Out of 112 cases, 70 cases (62.5%) were benign, 38 cases (33.92%) malignant and 4 cases (3.57%) were inconclusive. Mean age of presentation was 34.94 yrs with male to female ratio of 1.2:1. Ninety-nine cases (88.4%) were seen in anterior compartment, 12 cases (10.7%) in posterior compartment and 1case (0.9%) in middle compartment. Thymoma (26 cases) was the most common lesion followed by Non Hodgkin lymphoma (17 cases) and germ cell tumor (16 cases). Conclusion: Mediastinal lesions occur more commonly in males with higher frequency of benign lesions, among which thymoma is the predominant lesion.